2007
DOI: 10.1002/jssc.200700245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic modifier and temperature on the resolution of betamethasone and dexamethasone using a porous graphitic carbon column: Application to their identification and confirmation in human urine by LC‐ESI‐MS/MS

Abstract: The effects of temperature, organic modifier and the type of acid on the retention factor, the resolution and peak shape of betamethasone and dexamethasone are described. The study is performed using narrow bore porous graphitic carbon (PGC) columns online with diode-array detector (DAD) and ESI MS/MS. The results show that temperature affects the retention behaviour of the two compounds and ACN yields the best separation while no effect is obtained by changing the type of organic acid. The developed method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The effect of analytical conditions was investigated in detail. The measurements indicated that the column temperature and the type of organic modifier exert a marked impact on the separation while the type of the organic acid was negligible (Oueslati et al, 2007).…”
Section: Porous Graphitized Carbon As Stationary Phasementioning
confidence: 98%
“…The effect of analytical conditions was investigated in detail. The measurements indicated that the column temperature and the type of organic modifier exert a marked impact on the separation while the type of the organic acid was negligible (Oueslati et al, 2007).…”
Section: Porous Graphitized Carbon As Stationary Phasementioning
confidence: 98%
“…Use of formic acid in the mobile phases facilitated the production of precursor ion [M+H] + and maintained the pH of the mobile phases at 4.0. The HPLC column was maintained at 40 • C. In general, the resolution of analytes is better at higher temperature [27]. Also, higher temperatures reduce the time of analysis [28].…”
Section: Lc-ms/ms Optimizationmentioning
confidence: 99%